PHYSIOLOGICAL RESPONSES OF ARABICA COFFEE SEEDLINGS TREATED WITH POTASSIUM, BORON, AND TRICHODERMA UNDER DROUGHT STRESS - Rangga Sidik Nur Rohman; Mochamad Arief Soleh; Yudithia Maxiselly (UIN Sunan Gunung Djati Bandung, 2026)
Arabica coffee productivity recently has faced risk of climate change-induced drought and rising temperatures. This study evaluated the physiological responses of Arabica coffee seedlings treated with potassium (K), boron (B), and the biological agent Trichoderma spp. under drought stress. A screenhouse experiment was conducted by using a Randomized Block Design with eight treatment combinations and four replications. Drought was induced by withholding irrigation for 18 days, followed by a 15-day recovery period. Parameters measured included the chlorophyll index, stomatal density, and net assimilation rate (NAR). Findings indicated that the application of nutrient and biological inputs resulted in similar physiological values across all treatments. The leaf chlorophyll index remained stable between 43.47 and 48.83 SPAD units, while stomatal density was recorded within the range of 129.94 to 219.11 stomata mm -2. Furthermore, the net assimilation rate varied from 0.08913 to 0.41975 g m -2 week -1. While providing similar overall outcomes, the effects of drought stress tended to be counterbalanced by the treatments. Several combinations produced higher physiological values compared to the control, indicating their potential as alternative agronomic strategies to maintain seedling resilience under drought. This study establishes a baseline for understanding the interactive effects of multi-input strategies on early-stage coffee resilience.